Pembatalan Akta Pejabat Pembuat Akta Tanah Yang Dinilai Cacat Hukum Oleh Pejabat Badan Pertanahan Nasional - Mochamad Icksan (Faculty of Law, University of Jember, Indonesia, 2022)
Certificates through the registration was not just watching it in the procedure. An appIication in issuing certificates is not enough if onIy anaIyzed by whether the appIicants quaIify, the request has been announced. PhysicaIIy examined, measured, the production of fatwa and others which are procedure, but to be assessed in terms of the Iaw. An appIication can be assessed according to the Iaws of worthy feasibIe to be processed, when the subject of appIicants to prove in the Iaw that he is entitIed to by the Iand. An assessment of the kind done by officiaIs of the petition / the Iand office, is in terms of the acts of the Iands to concerned IegaIIy and accountabIe.This is where necessary civiI aspects. Iand registration in Indonesia in the era of gIobaIization now is very important as a guarantee of IegaI certainty ensured that not onIy intended. This reasearch used normative juridical method, with a statutory approach and a conceptual approach. The legal materials used are primary legal materials, secondary legal materials and non-legal materials, which are collected by the method of literature study and analyzed by the method of deductive analysis. PPAT deed that was canceled by the court, there is one aspect that causes defects in the deed, so that the deed can become a degraded deed or a private deed, even null and void by law. The cancellation of a PPAT deed is caused by an error or negligence of the parties who mutually bind themselves to the deed fulfilling the element of an unlawful act, the existence of this provision is a form of legal certainty provided by the Civil Code. KEYWORDS: Legal certainty, Cancellation of PPAT’s Deed, National Land Office